2010 10th International Conference on Hybrid Intelligent Systems 2010
DOI: 10.1109/his.2010.5600023
|View full text |Cite
|
Sign up to set email alerts
|

An integral approach for Geno-Simulated Annealing

Abstract: Global optimization is the problem of finding the global optimum of any given function in a certain search space. Simulated Annealing (SA) and Genetic Algorithms (GA) are among the well-known techniques used for global optimization. Adjusting the parameters of SA such as the temperature schedule and the neighborhood range plays an important role in the performance of the algorithm. Furthermore, many studies in literature showed that the best values for SA parameters depend on the optimization problem. We intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Digalakis and Margaritis developed two algorithms titled as the generational replacement model (GRM) and the steady state replacement model by making modifications on the genetic algorithm and monitored their performances on unconstrained test functions [12]. By combining the GA and SA algorithms, Hassan et al proposed the geno-simulated annealing (GSA) algorithm and implemented it on the most commonly used unconstrained test functions [13]. In order to obtain a better performance in the multidimensional search space, Chatterjee et al suggested the nonlinear variation of the known PSO, the non-PSO algorithm, and measured its performance on several unconstrained test functions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Digalakis and Margaritis developed two algorithms titled as the generational replacement model (GRM) and the steady state replacement model by making modifications on the genetic algorithm and monitored their performances on unconstrained test functions [12]. By combining the GA and SA algorithms, Hassan et al proposed the geno-simulated annealing (GSA) algorithm and implemented it on the most commonly used unconstrained test functions [13]. In order to obtain a better performance in the multidimensional search space, Chatterjee et al suggested the nonlinear variation of the known PSO, the non-PSO algorithm, and measured its performance on several unconstrained test functions [14].…”
Section: Introductionmentioning
confidence: 99%